Performance of three multiplex real-time PCR assays for simultaneous detection of 12 infectious pathogens in mice affected with respiratory and digestive diseases - Wang, Hye-young; Ahn, Jaeil; Lee, Jonghoon; Kang, Sang Chul; Kim, Hyunil (Frontiers in Veterinary Science, 2024)
Research quality can be improved with reliable and reproducible experimental results when animal experiments are conducted using laboratory animals with guaranteed microbiological and genetic quality through health monitoring. Therefore, health monitoring requires the rapid and accurate diagnosis of infectious diseases in laboratory animals. This study presents a performance evaluation of a commercially available multiplex real-time PCR (mRT-PCR) assay for the rapid detection of 12 infectious pathogens (Set 1: Sendai virus [SeV, formally murine respirovirus], Mycoplasma spp., Rodentibacter. pneumotropicus, and Rodentibacter heylii; Set 2: Helicobacter spp., Murine norovirus [MNV], Murine hepatitis virus [MHV], and Salmonella spp.; Set 3: Staphylococcus aureus,Streptobacillus moniliformis, Corynebacterium kutscheri, and Pseudomonas aeruginosa). The assay's detection limit ranged from 1 to 100 copies per reaction. Specificity testing involving various viruses and bacteria indicated no cross-reactivity between strains. Additionally, the assay exhibited good reproducibility, with mean coefficients of variation for inter-and intra assay variation below 3%. To evaluate the efficacy of the mRT-PCR assay, 102 clinical samples encompassing fecal and cecal specimens were analyzed. The resulting data were then compared with the findings from sequence analysis for validation. The overall positive rate was 52.9% (n = 54), with the mRT-PCR assay findings matching sequence analysis results (κ = 1). MHV (n = 29, 28.4%) was the most prevalent pathogen, followed by Helicobacter spp. (n = 28, 27.5%), R. heylii (n = 18, 17.6%), Mycoplasma spp.(n = 14, 13.7%), MNV (n = 12, 11.8%), S. aureus (n = 9, 8.8%), P. aeruginosa (n = 4, 3.9%), and R. pneumotropicus (n = 1, 0.9%). This assay offers a rapid turnaround time of 100 min, including 30 min for DNA preparation and 70 min for target DNA/RNA amplification. It ensures accuracy, minimizing false positives or negatives, making it a convenient tool for the simultaneous detection of infectious diseases in many samples. Overall, the proposed assay holds promise for the effective detection of the most important pathogens in laboratory animal health monitoring.